HUBUNGAN STRES KERJA DENGAN GANGGUAN KESEHATAN PADA PEKERJA PT.X BATAM TAHUN 2025 - Krismadies; Diina Maulina (Universitas Batam, 2025)
ABSTRACT Work stress is one of the factors that can affect workers’ physical health. This study aimed to determine the relationship between work stress levels and physical health disorders among employees of PT. X Batam. A cross-sectional design was applied with 42 respondents selected through purposive sampling. Data were collected using the DASS-30 questionnaire and observation, then analyzed using the chi-square test. The findings revealed that most respondents experienced physical health disorders, including cardiovascular disorders (76.2%), sleep disorders (81%), digestive problems (90.5%), musculoskeletal disorders (59.5%), and decreased immune function (88.1%). Statistical analysis indicated a significant association between work stress levels and all five types of physical health disorders (p < 0.05), with the strongest correlation observed in digestive problems. This study highlights the importance of workplace stress management as a preventive strategy to reduce physical health disorders and enhance employee well-being. Kata kunci: stres kerja, gangguan kesehatan pekerja